2007
DOI: 10.1021/jm070393d
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies of Neoclerodane Diterpenes from Salvia divinorum:  Preparation and Opioid Receptor Activity of Salvinicin Analogues

Abstract: Further modification of salvinorin A (1a), the major active component of Salvia divinorum, has resulted in the synthesis of novel neoclerodane diterpenes with opioid receptor affinity and activity. We report in this study that oxadiazole 11a and salvidivin A (12a), a photooxygenation product of 1a, have been identified as the first neoclerodane diterpenes with kappa antagonist activity. This indicates that additional structural modifications of 1a may lead to analogues with higher potency and utility as drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 36 publications
3
87
0
Order By: Relevance
“…Salvinorin G (7) was also shown to have modest binding affinity (Lee et al, 2005b), which is abolished on hydrolysis of the C-1 acetate moiety (31) . More recently, C-12 furan-modified salvinicin A (17; K i ϭ 390 nM) and salvidivin A (19; K i ϭ 440 nM) were identified as KOP receptor ligands, 19 being identified as the first naturally occurring neoclerodane with KOP antagonist activity (Simpson et al, 2007).…”
Section: A Structure-activity Relationships Of Analogsmentioning
confidence: 99%
See 3 more Smart Citations
“…Salvinorin G (7) was also shown to have modest binding affinity (Lee et al, 2005b), which is abolished on hydrolysis of the C-1 acetate moiety (31) . More recently, C-12 furan-modified salvinicin A (17; K i ϭ 390 nM) and salvidivin A (19; K i ϭ 440 nM) were identified as KOP receptor ligands, 19 being identified as the first naturally occurring neoclerodane with KOP antagonist activity (Simpson et al, 2007).…”
Section: A Structure-activity Relationships Of Analogsmentioning
confidence: 99%
“…There has been much recent interest into evaluation of the SAR of the furan moiety on the C-12 position of ring C (Munro et al, 2005b;Harding et al, 2006a;Simpson et al, 2007;Yang et al, 2009). Epimerization of C-12 (12-epi-1) resulted in a modest drop in KOP receptor binding affinity compared with the natural isomer (K i ϭ 41 versus 2.5 nM; Fig.…”
Section: Modifications To the C-12 Furanmentioning
confidence: 99%
See 2 more Smart Citations
“…A KOPR antagonist has been shown to have antidepressant-like effects preclinically (Todtenkopf et al, 2004). In a recent study, two derivatives of Sal A, oxadiazole and salvidivin A, have been reported to act as KOPR antagonists in the [ 35 S]GTP␥S binding assay (Simpson et al, 2007). It is encouraging that Sal A may be used as a lead compound to develop KOPR antagonists with therapeutic potential in, for example, clinical depression.…”
Section: Regulation Of Koprmentioning
confidence: 99%